Auditoria financiera de las cuentas por cobrar clientes de la Promotora Fundadores Agencia de Seguros Ltda del 01 enero al 30 de junio de 2012. (2012)
The financial audit process is made to due accounts from customers of the developing Founders Insurance Agency Ltd, a company in the service sector, which has a large portfolio specializing in insurance sales. The mission of the Colombian Financial Superintendence is to conduct external monitoring and control the entities providing insurance services, but in our particular case the ones that perform such internal control are the comptroller and audit department, which support its work by acknowledge of the business, an inspection plan and the necessary procedures for a customer’s review, to determine the reasonableness of the accounts and finally give a recommendation that demonstrates whether if there are effective the established processes by Suramericana during the first half of 2012.